Cosmogenic radionuclides : theory and applications in the terrestrial and space environments - Beer, Jürg (Physics of earth and space environments, 2012)
Cosmogenic radionuclides are radioactive isotopes which are produced by natural processes and distributed within the Earth system. With a holistic view of the environment the authors show in this book how cosmogenic radionuclides can be used to trace and to reconstruct the history of a large variety of processes. They discuss the way in which cosmogenic radionuclides can assist in the quantification of complex processes in the present-day environment. This book aims to demonstrate to the reader the strength of analytic tools based on cosmogenic radionuclides, their contribution to almost any field of modern science, and how these tools may assist in the solution of many present and future problems that we face here on earth"--Back cover.